Decolonising the Archive. Rethinking Audiovisual Heritage in the ERT Collection - Pritsas, Gregory (Unlocking Television Archives in the Digital Era. 16th Media Mutations International Conference, 2026)
Archives are not neutral repositories but active agents in shaping cultural memory, delineating inclusion and exclusion through their classificatory logics and curatorial priorities. The Greek National Broadcaster (ERT) archive, a vast repository of radio and television material, provides a critical case study for examining how state-controlled institutions embed hierarchies of visibility and erasure within archival structures. This paper interrogates the epistemic frameworks underpinning the ERT archive, situating them within national identity formation, transnational media flows, and institutional power dynamics. Which voices and histories have been marginalised? How do archival protocols reinforce dominant historiographies? What role can digitisation and participatory models play in counter-archival interventions? Drawing on politically contentious broadcasts, entertainment programming, and obscured narratives, this paper explores strategies for reconfiguring archival methodologies to amplify silenced perspectives. It advocates for oral histories, community-led curation, and digital remediation as tools to destabilise entrenched power asymmetries. In dialogue with contemporary debates on the decolonisation of media heritage, this study positions the archive as a contested and evolving space, where competing narratives negotiate cultural memory in the digital age.